2018
DOI: 10.1111/jpg.12705
|View full text |Cite|
|
Sign up to set email alerts
|

The Geochemical Characteristics of the Oligocene – Lower Miocene Menilite Formation in the Polish and Ukrainian Outer Carpathians: A Review

Abstract: The principal source rocks in the Outer Carpathians are organic‐rich shales in the Oligocene to Lower Miocene Menilite Formation. The average total organic carbon (TOC) content in the Menilite Formation is 4–8 wt%; the maximum measured is 26 wt%. Organic matter (OM) is oil‐prone Type II kerogen derived mainly from algae and cyanobacteria which was deposited under euxinic conditions. The thermal maturity of the Menilite shales varies significantly within the Outer Carpathians, both vertically in relation to bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…(Summary after ten Haven et al, 1993;Lafargue et al, 1994;Kotarba and Koltun, 2006;Matyasik and Dziadzio, 2006;Oszczypko et al, 2006;Pawlewicz, 2006;Slaczka et al, 2006;Krobicki et al, 2012;Kotarba et al, 2013;Slaczka et al, 2014;Krzywiec et al, 2014;Machowski et al, 2017;Waskowska et al,2018;Kosakowski et al,2018 this issue)…”
Section: North Carp Pa Pa P Thian Fold-thrust Province Thian Fold-thrunclassified
“…(Summary after ten Haven et al, 1993;Lafargue et al, 1994;Kotarba and Koltun, 2006;Matyasik and Dziadzio, 2006;Oszczypko et al, 2006;Pawlewicz, 2006;Slaczka et al, 2006;Krobicki et al, 2012;Kotarba et al, 2013;Slaczka et al, 2014;Krzywiec et al, 2014;Machowski et al, 2017;Waskowska et al,2018;Kosakowski et al,2018 this issue)…”
Section: North Carp Pa Pa P Thian Fold-thrust Province Thian Fold-thrunclassified
“…The SPI of the Lower Oligocene Lower Menilite succession is higher (16 tHC/m²) than that Boote et al, 2018) are concentrated in the Boryslav-Pokuttya nappe of Ukraine, where the Upper Menilite Member has a similar thickness to that in the external part of the Skyba nappe (e.g. Vialov et al, 1988;Kosakowski et al, 2018). It can therefore be proposed that the prolific nature of the Boryslav-Pokuttya petroleum system is mainly related to the large thickness of the Menilite Formation, the exceptional high SPI in this region, and the occurrence of these source rocks within the oil window.…”
Section: Source Rock Potentialmentioning
confidence: 99%
“…Petroleum production began in 1854 with the discovery of the Boryslav oil field, one of the largest onshore oilfields in Europe (Kotarba et al, 2007). The Lower Oligocene -Lower Miocene Menilite Formation is the primary source rock interval in this region (Köster et al, 1998;Kotarba et al, 2006;Kosakowski et al, 2018). Age-equivalent "Maikopian" source rocks are important elsewhere in the Paratethys realm including the Alpine Foreland Basin, Caucasus foredeep, Kura Basin and South Caspian Basin (Sachsenhofer et al, 2018a(Sachsenhofer et al, , 2018b.…”
Section: Introductionmentioning
confidence: 99%
“…The newer publications of Kotarba et al (2013Kotarba et al ( , 2014 also confirmed the best generation potential of menilite shales. Recently, the influence of changes of deposition facies on the generation potential of the Menilite Beds was examined (Kosakowski et al, 2018) and it was found that there is no direct correlation in this case. (Jankowski 2008, Jankowski, Probulski, 2011.…”
Section: Introductionmentioning
confidence: 99%